2018
DOI: 10.3389/fmars.2018.00429
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities in the East and West Fram Strait During Sea Ice Melting Season

Abstract: Climate models project that the Arctic Ocean may experience ice-free summers by the second half of this century. This may have severe repercussions on phytoplankton bloom dynamics and the associated cycling of carbon in surface waters. We currently lack baseline knowledge of the seasonal dynamics of Arctic microbial communities, which is needed in order to better estimate the effects of such changes on ecosystem functioning. Here we present a comparative study of polar summer microbial communities in the ice-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 123 publications
13
85
0
Order By: Relevance
“…This pattern fits the known global trend of archaeal enrichment in epipelagic waters (Karner et al, 2001;Herndl et al, 2005;Kirchman et al, 2007;Varela et al, 2008;Schattenhofer et al, 2009) and was also observed in other regions of the Arctic Ocean (Amano-Sato et al, 2013). Altogether, the observed cell numbers in the surface waters were well within the range of previous observations in the Fram Strait waters (Piontek et al, 2014;Fadeev et al, 2018;Engel et al, 2019). Below the upper 100 m the observed bacterioplankton cell abundances were lower than the ones previously reported from the eastern Fram Strait by Quero et al (2019).…”
Section: Bacterioplankton Communities Strongly Change In Cell Abundansupporting
confidence: 90%
See 4 more Smart Citations
“…This pattern fits the known global trend of archaeal enrichment in epipelagic waters (Karner et al, 2001;Herndl et al, 2005;Kirchman et al, 2007;Varela et al, 2008;Schattenhofer et al, 2009) and was also observed in other regions of the Arctic Ocean (Amano-Sato et al, 2013). Altogether, the observed cell numbers in the surface waters were well within the range of previous observations in the Fram Strait waters (Piontek et al, 2014;Fadeev et al, 2018;Engel et al, 2019). Below the upper 100 m the observed bacterioplankton cell abundances were lower than the ones previously reported from the eastern Fram Strait by Quero et al (2019).…”
Section: Bacterioplankton Communities Strongly Change In Cell Abundansupporting
confidence: 90%
“…At the time of sampling in June-July 2016, chlorophyll a concentrations showed a developed phytoplankton bloom across the Strait (Table S1). Thus, fitting the interannual trend of summerly phytoplankton bloom conditions in the western icecovered EGC and the eastern ice-free WSC (Nöthig et al, 2015;Fadeev et al, 2018).…”
Section: Bacterioplankton Communities Strongly Change In Cell Abundanmentioning
confidence: 99%
See 3 more Smart Citations